Precocious Degenerative Arthropathy And Bluish Patches On Ears : Ochronosis And Alkaptonuria - Mahajan Vikram K; Sharma Nand Lal; Yadav Ravi S (Wolters Kluwer Medknow Publications, 2004)
Alkaptonuria is a rare, autosomal recessive disorder of phenylalanin/tyrosine metabolism due to congenital deficiency of the enzyme homogentisic acid oxidase. The diagnosis is clinical and the triad of homogentisic aciduria, ochronosis and precocious degenerative arthritis is characteristic. Its diagnosis in infancy and early therapeutic intervention help delaying its complications. These patients may remain undiagnosed until the darkening of urine soaked diapers is noticed or the early degenerative arthropathy develops. This paper describes two cases of alkaptonuria presenting late in life; one of them had associated hyperthyroidism.